Nutrient intake, Digestibility and Rumen Fermentation Parameters in Buffalo Bulls fed Cumbu Napier (COBN-5) Fodder - Madesh, M; Kishore, K Raja; Kumar, D Srinivas; Anitha, Alapati (Indian Journal of Animal Nutrition, 2021)
In the present study, Cumbu Napier (COBN-5) fodder was evaluated for nutrient intake, digestibility and rumen fermentation pattern in buffalo bulls. The average DMI (kg/d) of buffalo bulls is 6.01 and met the requirements for maintenance indicating that the fodder is palatable. The pre cent DCP (8.74) and TDN (56.05) in the fodder consumed met the ICAR standards and is attributed to the better nutrient digestibilities. The DM, DCP, TDN and ME intakes per Wkg0.75 in buffalo bulls fed ad libitum of COBN-5 fodder were 73.03, 6.38, 40.93 and 0.15, respectively. The digestibility co-efficients (%) of gross nutrients and fibre fractions in COBN-5 fodder evinced better utilization and is higher compared to many Napier grass varieties. Nitrogen, calcium and phosphorus utilization reported positive balances and met the requirements for maintenance in buffalo bulls. Rumen fermentation parameters revealed that rumen pH values were highest at 0 h and declined to minimum by 6 h post feeding, while TVFA reached peak at 6 h post feeding and NH3-N reached peak at 2 h post feeding and later followed a decreasing trend which is attributed to better microbial fermentation. It is concluded that feeding COBN-5 fodder ad libitum to buffalo bulls had no adverse effects and evinced better nutrient utilization, rumen fermentation parameters and plane of nutrition.